2021
DOI: 10.7498/aps.70.20210920
|View full text |Cite
|
Sign up to set email alerts
|

Improving the sensitivity of an optically pumped rubidium atomic magnetometer by using of a repumping laser beam

Abstract: For the experimental implementation of an optically pumped atomic magnetometer, the magnetic resonance signal with a narrow linewidth and a high signal-to-noise ratio (SNR) is required for achieving a high sensitivity. Using 795-nm laser as both the pumping and the probe laser, we compare the magnetic resonance signals from different rubidium atomic vapor cells and investigate the variations of magnetic resonance signals with temperature. Optimized magnetic resonance signal is achieved with a paraffin-coated r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 22 publications
0
3
0
Order By: Relevance
“…This result laid a foundation for subsequent employing Stokes operator polarization-squeezed light [ 32 ] to improve SNR, and further improve the sensitivity of the magnetometer. Compared to previous works [ 32 , 41 ], FID type rubidium atomic magnetometer more broadly and accurately measured magnetic fields, and was not limited to tracking magnetic field in real-time. In addition, we preliminarily demonstrated quantum enhancement in a single-beam linearly polarized Faraday rotation magnetometer, via 795 nm Stokes operator polarization-squeezed light; the sensitivity was improved from 28.3 pT/ to 19.5 pT/ [ 32 ].…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…This result laid a foundation for subsequent employing Stokes operator polarization-squeezed light [ 32 ] to improve SNR, and further improve the sensitivity of the magnetometer. Compared to previous works [ 32 , 41 ], FID type rubidium atomic magnetometer more broadly and accurately measured magnetic fields, and was not limited to tracking magnetic field in real-time. In addition, we preliminarily demonstrated quantum enhancement in a single-beam linearly polarized Faraday rotation magnetometer, via 795 nm Stokes operator polarization-squeezed light; the sensitivity was improved from 28.3 pT/ to 19.5 pT/ [ 32 ].…”
Section: Discussionmentioning
confidence: 94%
“…This indicated that the probe light with large frequency detuning was a better choice for compatibility with the polarization-squeezed light. In the Mz magnetometer, which we demonstrated, there was only a circularly polarized light resonated with the atomic transition line and it was not very compatible with the squeezed light [ 41 ]. In FID type rubidium atomic magnetometer system, the probe light with large frequency detuning fully met the introduction conditions of the polarization-squeezed light; however, in our system, optimization to make the system noise reach the PSN before the introduction of squeezed light was crucially important, such as the intensity fluctuation of the light, the inhomogeneity of the magnetic field, and etc.…”
Section: Sensitivity Analysis and Discussionmentioning
confidence: 99%
“…To improve the sensitivity and other performance indicators of OPMs that can be applied in a geomagnetic field, various new physical mechanisms and technologies have been applied to OPMs [16,19,20]. In recent years, with the development of laser technology, the application of lasers in OPMs has become a focus of attention owing to its good spectral line selectivity and stronger light intensity than spectral lamps.…”
Section: Introductionmentioning
confidence: 99%